Synthesis of MAX phases Nb2CuC and Ti2(Al0.1Cu0.9)N by A-site replacement reaction in molten salts. Issue 12 (2nd December 2019) - Ding, Haoming; Li, Youbing; Lu, Jun; Luo, Kan; Chen, Ke; Li, Mian; Persson, Per O. Å.; Hultman, Lars; Eklund, Per; Du, Shiyu; Huang, Zhengren; Chai, Zhifang; et al.
ABSTRACT: New MAX phases Ti2 (Al x Cu1− x )N and Nb2 CuC were synthesized by A-site replacement by reacting Ti2 AlN and Nb2 AlC, respectively, with CuCl2 or CuI molten salt. X-ray diffraction, scanning electron microscopy, and atomically resolved scanning transmission electron microscopy showed complete A-site replacement in Nb2 AlC, which lead to the formation of Nb2 CuC. However, the replacement of Al in Ti2 AlN phase was only close to complete at Ti2 (Al0.1 Cu0.9 )N. Density-functional theory calculations corroborated the structural stability of Nb2 CuC and Ti2 CuN phases. Moreover, the calculated cleavage energy in these Cu-containing MAX phases are weaker than in their Al-containing counterparts. GRAPHICAL ABSTRACT: IMPACT STATEMENT: The preparation of MAX phases Nb2 CuC and Ti2 (Al0.1 Cu0.9 )N were realized by A-site replacement in Ti2AlN and Nb2AlN, respectively.